PERANCANGAN DAN IMPLEMENTASI JARINGAN FAILOVER MENGGUNAKAN PROTOKOL SPANNING TREE PADA PT. PLN UP3B KALIMANTAN TIMUR - Djumhadi Djumhadi; Riovan Styx Roring (Jurnal Ilmiah Matrik, 2020)
The availability of electricity is very reliable as a main of supporting component in development progress and economic growth. PT. PLN as an authorized implementation unit for distributing and regulating electricity supply from the power plant to the transmission line requires a reliable network communication system for its operations, as a facility to connect all of its main substations. The disruption of the information network is an important thing that must be avoided in the company so that it does not interfere the distribution of information. The reliable information distribution methods from the main office to the branch offices should be failover that uses backup links in all branch offices as a solution to keep the information network system reliable by using the protocol of spanning tree and VLAN configuration on the routers and manageable switches. Having used the failover method on a network system, it is expected to help the company to always keep reliable in distributing information to all substations so that information loss can be drastically reduced.